Trimodal system for in vivo skin cancer screening with combined optical coherence tomography‐Raman and colocalized optoacoustic measurements. Issue 6 (26th February 2018) - Varkentin, Arthur; Mazurenka, Mikhail; Blumenröther, Elias; Behrendt, Lea; Emmert, Steffen; Morgner, Uwe; Meinhardt‐Wollweber, Merve; Rahlves, Maik; Roth, Bernhard
Abstract : Optical coherence tomography (OCT) has evolved to a powerful tool for medical applications. Yet, often there are insurmountable limits, like the penetration depth of OCT, arising from physical properties of this measurement technique. In other cases, additional information is required or would be helpful to allow robust, pathologically relevant conclusions. Therefore, a multimodal system for thickness assessment of lesions and, in particular, melanoma was developed, combining OCT, optoacoustics and (resonance) Raman spectroscopy. Abstract : A new multimodal system for rapid, noninvasive in vivo skin cancer screening is presented, combining optical coherence tomography (OCT) and optoacoustic (OA) modalities to provide precise tumor depth determination with a Raman spectroscopic modality capable of detecting the lesion type and, thus, providing diagnostic capability. Both OA and Raman setups use wide field skin illumination to ensure the compliance with maximum permissible exposure (MPE) requirements. The Raman signal is collected via the OCT scanning lens to maximize the signal‐to‐noise ratio of the measured signal while keeping radiation levels below MPE limits. OCT is used to optically determine the tumor thickness and for volumetric imaging whereas OA utilizes acoustic signals generated by optical absorption contrast for thickness determination at potentially higher penetration depths compared to OCT. Preliminary results of first clinical trials using our setup are presented. The measured lesion depth is in good agreement with histology results, while Raman measurements show distinctive differences between normal skin and melanocytic lesions, and, moreover, between different skin areas. In future, we will validate the setup presented for reliable detection of pathophysiological parameters, morphology and thickness of suspicious skin lesions.